Pengembangan Model Teknologi Blockchain untuk Meningkatkan Transparansi Pengelolaan Sampah - Inayatulloh, Inayatulloh (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Waste management is a series of activities that involve collecting, transporting, processing, and recycling waste materials. The aim of waste management is to reduce the negative impact of waste on the environment and humans. This process includes sorting types of waste, applying the principles of reduce, reuse, recycle, and handling according to the characteristics of each type of waste. The problem with the current waste management mechanism is that there is no transparency regarding the origin of the waste, distribution channels, or movement from the waste source to the waste recycling management site. The collected waste cannot be transparently detected at its source and distribution channels. Thus, the aim of this research is to increase the transparency of waste management using blockchain technology. Blockchain technology can provide a high level of transparency in waste management by using peer-to-peer validation from every stakeholder involved in waste management. Blockchain technology in waste management provides data security with the immutable concept of blockchain technology. The research method uses a qualitative approach by studying waste management, parties involved in waste management, and blockchain technology. The result of this research is a model for adopting waste management using blockchain technology and simulation with Ganache Blockchain Framework.